Towards spruce-type photosystem II: consequences of the loss of light-harvesting proteins LHCB3 and LHCB6 in Arabidopsis - Ilíková, Iva; Ilík, Petr; Opatíková, Monika; Arshad, Rameez; Nosek, Lukáš; Karlický, Václav; Kučerová, Zuzana; Roudnický, Pavel; Pospíšil, Pavel; Lazár, Dušan; Bartoš, Jan; Kouřil, Roman (Plant physiology, 2021)
The largest stable photosystem II (PSII) supercomplex in land plants (C2S2M2) consists of a core complex dimer (C2), two strongly (S2) and two moderately (M2) bound light-harvesting protein (LHCB) trimers attached to C2 via monomeric antenna proteins LHCB4-6. Recently, we have shown that LHCB3 and LHCB6, presumably essential for land plants, are missing in Norway spruce (Picea abies), which results in a unique structure of its C2S2M2 supercomplex. Here, we performed structure-function characterization of PSII supercomplexes in Arabidopsis (Arabidopsis thaliana) mutants lhcb3, lhcb6, and lhcb3 lhcb6 to examine the possibility of the formation of the "spruce-type" PSII supercomplex in angiosperms. Unlike in spruce, in Arabidopsis both LHCB3 and LHCB6 are necessary for stable binding of the M trimer to PSII core. The "spruce-type" PSII supercomplex was observed with low abundance only in the lhcb3 plants and its formation did not require the presence of LHCB4.3, the only LHCB4-type protein in spruce. Electron microscopy analysis of grana membranes revealed that the majority of PSII in lhcb6 and namely in lhcb3 lhcb6 mutants were arranged into C2S2 semi-crystalline arrays, some of which appeared to structurally restrict plastoquinone diffusion. Mutants without LHCB6 were characterized by fast induction of non-photochemical quenching and, on the contrary to the previous lhcb6 study, by only transient slowdown of electron transport between PSII and PSI. We hypothesize that these functional changes, associated with the arrangement of PSII into C2S2 arrays in thylakoids, may be important for the photoprotection of both PSI and PSII upon abrupt high-light exposure.
Keywords: proteiny vázající chlorofyl; Photosystem II Protein Complex; Arabidopsis; proteiny huseníčku; fotosystém II (proteinový komplex); Picea; smrk; Arabidopsis Proteins; Chlorophyll Binding Proteins